Evaluation of Regional Domestic Waste Water Treatment Plant Performance in Cimahi City - Mila Dirgawati; Mohamad Rangga Sururi; Wili Wiliana; Nining Widiawati (Universitas Diponegoro, 2021)
Domestic wastewater treatment plant performance (WWTP) currently refers to stringent wastewater quality standards (Minister of Environment and Forestry Regulation No. 68 of 2016) considering potential environmental degradation because of pollutants in the wastewater. This study evaluated the performance of the Regional Domestic WWTP in Cimahi City. Cimahi has 10 WWTPs which were operated by an Anaerobic Baffled Reactor system. Periodic monitoring only measured the wastewater characteristics after treatment with parameters: total suspended solids (TSS), ammonia, chemical oxygen demand(COD), biological oxygen demand(BOD), and oil and grease. Therefore, wastewater characteristics were measured before and after treatment at selected WWTP during peak and non-peak hours, with TSS, ammonia, and COD. Important hydraulic factors were also measured: flow velocity at peak and non-peak hours, hydraulic detention time, and sludge height. Effluent from all WWTPs did not meet the standard. However, WWTPs with detention time >2 days produced parameter concentrations closed to the maximum value. The selected WWTP has a 5.7days detention time with removal efficiency for COD 57.52%, and TSS 42.56%, during peak period and COD 60.19% and TSS 34.84% for a non-peak period, but ammonia concentration did not decrease. Overall, WWTP has not been able to meet quality standards and the quality.